POTENTIAL FOR TAROMPA TRADITIONAL CRAFTS IN THE CREATIVE INDUSTRIAL ERA IN WEST SUMATERA AND THE DESIGN DEVELOPMENT STRATEGY - Amrizal Amrizal; Sumadi sumadi (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
ABSTRACT Tarompa Datuak is the fruit of creativity and innovation developed by traditional Minangkabau leather crafts-men. Tarompa Datuak traditional crafts become one of the forms of the creative industry sub-sector in West Sumatra. The creative industry based on local culture has an important role to improve the economy of a society amidst the global cultural arena. The development of the creative industry sector of an area is insepa-rable from the ability of local communities to innovate and explore the cultural richness of their regions cre-atively. Local culture with economic value can be explored creatively into a marketable product in the global market. Tarompa Datuak’s exploration can be done through optimal design development, not only for eco-nomic purposes or providing welfare for the supporting community, but also as part of the preservation of the local cultural products. The method used in the research is research and development methods, namely research conducted to develop products or improve products gradually, ranging from analyzing development needs, designing, creating, implementing to evaluating product feasibility and revising so that new products are developed truly empirically tested.